Dielectric properties of novel nanocomposites based on PVA incorporating CuO nanoparticles - Erol, Ibrahim; Dere, Aysegul; Yalcin, Mesut; Khamidov, Gofur; Mansour, Shehab A.; Tukhtaev, Davlat; Yakuphanoğlu, Fahrettin (Springer, 2025)
Copper(II) oxide nanoparticles (CuO NPs) were incorporated into the blend of methacrylate-based poly 2-(4-fluorophenyl)-2-oxoethyl-2-methylprop-2-enoate (PFPAMA) polymer and polyvinyl alcohol (PVA) at different feed rates by hydrothermal method. The average particle size of CuO nanoparticles produced via solution plasma was 20-25 nm, as determined by TEM. The structural and morphological properties of the nanocomposites were determined by SEM, EDX, and FTIR spectroscopy. The dielectric properties of the nanocomposites were investigated in detail by impedance spectroscopy. The real dielectric constant (epsilon') reached a maximum value of approximately 6 at low frequencies for the 5% CuO-doped nanocomposite, indicating enhanced interfacial polarization (Maxwell-Wagner-Sillars polarization). Comparatively, epsilon' values for 3% and 7% CuO doping were approximately 4 and 3, respectively, suggesting reduced polarization capacity. Similarly, the imaginary dielectric constant (epsilon '') exhibited the highest value (similar to 0.6) at low frequencies for the 5% CuO addition, signifying increased energy losses. Impedance analysis revealed a significant decrease in resistance at higher CuO NPs contents, and the nanocomposite incorporating 7% CuO achieved the lowest impedance values (similar to 1.5 x 10(7) Omega). These results indicate that CuO addition improves the dielectric and electrical properties to the optimum level (5%), whereas excessive CuO NPs addition (7%) creates structural irregularities and degrades performance. The findings highlight the potential applications of these nanocomposites in electronic and energy storage devices.
Keywords: Electrical-Conductivity